When does the manufacturing reshoring strategy create value?. Issue 3 (June 2022) - Karatzas, Antonios; Ancarani, Alessandro; Fratocchi, Luciano; Di Stefano, Cristina; Godsell, Janet
Abstract: Reshoring has gained a lot of attention recently by academics and practitioners alike, and is promising to become even more relevant in the aftermath of the COVID-19 pandemic. Building on earlier research on the effects of reshoring announcements on the short-term market value of the firm, this work employs an event-study methodology and aims to understand under which circumstances the market perceives reshoring as potentially more (or less) value-creating. The analysis of a sample of 64 reshoring instances from 2005 to 2019, announced by 54 firms from eight developed economies, suggests that investors are more confident in the firm's future cash-flow potential when: a) it invests in productive activities at home, instead of overseas, i.e. 'kept-from-offshoring' (as opposed to actual relocations of activities, i.e. 'back-reshoring'); b) the reshoring instance is communicated as a 'plan' (rather than a fixed 'decision'); c) no state- or government-induced financial incentives are involved; d) the motivations are primarily 'cost-efficiency seeking' (rather than 'customer perceived value seeking'). Highlights: This work uses the event-study methodology to evaluate the effect of reshoring announcements on firms' market value. It identifies conditions under which reshoring is perceived as potentially more value-creating. 'Kept-from-offshoring' endeavours, communicated as 'plans', not involving monetary incentives, generate relatively higher returns. Cost-efficiency seeking motivations are seen more positively than customer perceived value seeking ones. The results should be treated with caution due to the small sample size of reshoring announcements eligible for the analysis.